Blood‐brain barrier insulin resistance decreases insulin uptake and increases amyloid beta uptake in Alzheimer's disease brain: Developing topics. (7th December 2020) - Zhou, Andrew L; Swaminathan, Suresh K; Gali, Chaitanya C; Bruinsma, Tyler J; Curran, Geoffry L; Sarma, Vidur V; Decklever, Teresa; Sharda, Nidhi; Wang, Lushan; Min, Paul H; Lowe, Val J; Kandimalla, Karunya K
Abstract: Background: Decreased brain insulin levels exacerbate cognitive decline in AD. Insulin in the brain is derived from systemic circulation via the blood‐brain barrier (BBB). We hypothesize that type II diabetes (T2D) sequelae and Aβ peptide exposure disrupt insulin signaling at the BBB and inhibit insulin delivery to brain. Further, we propose insulin signaling defects at the BBB contribute to Aβ accumulation in AD brain. Methods: The following studies were performed in wild‐type (WT) mice on regular chow (RC) diet, WT mice on high fat (HF) diet (manifest insulin resistance), APP/PS1 transgenic mice on RC diet (overexpress Aβ), and APP/PS1 mice on HF diet (overexpress Aβ + insulin resistance). After femoral injection of 125 I‐insulin or 125 I‐Aβ42, the brain accumulation was monitored between 0‐40 min by dynamic SPECT/CT imaging. The brain influx clearance was estimated by the slope obtained from Gjedde‐Patlak graphical analysis. Cerebral microvessels were harvested, and reverse phase protein array (RPPA) was performed to examine insulin signaling changes. Differentially expressed targets were subsequently confirmed by western blot. The brain influx of 125 I‐insulin and 125 I‐Aβ42 were further assessed in WT‐RC mice after internal carotid infusion with AG1024, a kinase inhibitor of the insulin receptor (IR) and insulin‐like growth factor receptor (IGF‐1R). Results: Compared to WT‐RC, 125 I‐insulin influx was decreased in WT‐HF and APP/PS1‐RC, and was further decreased in APP/PS1‐HF (4.1, 3.4, 3.5 and 2.6*10 ‐4 mL/min, respectively). Compared to WT‐RC, 125 I‐Aβ42 influx was increased in WT‐HF and APP/PS1‐RC (8.6, 28 and 23*10 ‐4 mL/min, respectively). RPPA analysis revealed global disruptions in BBB insulin signaling pathways. Western blots confirmed reduced expression of IR‐β, p‐AKT and p‐GSK3β in WT‐HF and APP/PS1‐RC compared to WT‐RC. Moreover, the largest decreases were observed in APP/PS1‐HF. Infusion with AG1024 was shown to decrease 125 I‐insulin influx, but increase 125 I‐Aβ42 influx. Conclusions: Both T2D and AD mice exhibited decreased brain influx of insulin and increased influx of Aβ42. This was associated with altered expression/activity of insulin signaling kinases at the BBB. Further, IR and/or IGF‐1R kinase activity were shown to differentially regulate BBB trafficking of insulin and Aβ42. Thus, BBB insulin signaling is important for delivering insulin to brain and restricting pathological uptake of Aβ.